Bandwidth Management Design Using the Simple Queue Method in Mikrotik RouterOS and The Winbox Application - Adika May Sari; Desy Suryani; Desri Yani; Rosmita Rosmita; Ahmad Rafik (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The function of bandwidth is to manage network bandwidth so that each network user can get the same bandwidth even though there are many users on the network. The use of the internet and computer networks is needed to support company operations. bandwidth requirements used are not small. In many companies, they have to get an internet connection for their individual needs and because the internet speed is only 10 Mbps, if it is not used according to the needs of the job, it will interfere with other workers who want to use the internet at PT. Five Main Techniques. To realize good bandwidth management, therefore the author will make bandwidth management with the simple queue method so that PT. Panca Teknik Utama has a network that can be used stably and according to the needs of each user even though many are using the internet simultaneously. To be able to make bandwidth management the author uses the observation method, interview method, and literature study method to collect data and supporting devices for making this bandwidth management are Mikrotik RouterOS and the Winbox application.